Aqueous extraction of hemicelluloses from spruce – From hot to warm. (January 2016) - Rissanen, Jussi V.; Murzin, Dmitry Yu.; Salmi, Tapio; Grénman, Henrik
Highlights: Extraction of hemicelluloses from wood was demonstrated at as low as 90 °C. The reaction mechanisms at low temperature are identical to high temperatures. The correlation of pH with conversion was confirmed in a very large temperature range. Obtained quantitative extraction parameters were demonstrated to apply under 170 °C. The results show in detail the early stages of extraction and open up new process paths. Abstract: Aqueous extraction of hemicelluloses from spruce sapwood was performed at 90 °C and 110 °C. One of the main goals was to study if the same reaction mechanisms are valid at low temperatures as the ones observed previously at higher temperatures. An intensified cascade reactor system with a high liquid–solid ratio (∼180) was used in the experiments. Differences between the sugar specific extraction rates were observed especially in the beginning of the extraction processes. The experimental results fitted well to a kinetic model developed at higher temperatures, which confirms that the dissolution occurs with the same mechanisms at low temperature. Moreover, the correlation of the pH with the amount of sugars dissolved concurred with previous observations. The results contradict the assumption that low temperature dissolution would not occur and they help in studying the early stages of extraction as the kinetics are considerably slowed down.